I don't want to hear about it: Rational ignorance among duty-orientd consumers - Karine Nyborg (University of Oslo, Department of Economics, 2008)
Individuals with a preference for keeping moral obligations may dislike learning that voluntary contributions are socially valuable: Such information can trigger unpleasant feelings of cognitive dissonance. I show that if initial beliefs about the social value of contributions are sufficiently low, duty-oriented consumers are willing to pay to avoid information. Attitude campaigns can increase contributions from such consumers by providing them with unwanted information. Consequentialist warm glow types with low initial beliefs, however, will seek low-cost information on their own initiative; thus, campaigns will have less effects for such consumers.
Keywords: D11; D62; D64; D89; H41; Q21; 330; Voluntary contributions; public goods; responsibility; altruism; information campaigns; cognitive dissonance; Öffentliches Gut; Soziale Werte; Informationsverhalten; Konsumentenverhalten; Verantwortung; Theorie